Pyomyositis in children: report of three cases and review of the literature - Gigante, C. (J Orthop Traumatol, 2007)
In temperate places, pyomyositis is uncommon in children and adolescents. We report 3 cases of pyomyositis in boys aged 11, 13 and 16 years. Staphylococcus aureus was the etiologic agent in all cases. Antibiotics therapy alone, or associated to surgical treatment was performed to resolve the infections. We describe the clinical and radiological work-up used to arrive at a diagnosis, and review the literature on this infection, which could be easily misdiagnosed because of its rarity outside of tropical climates.